1983
DOI: 10.1111/j.1440-1681.1983.tb00188.x
|View full text |Cite
|
Sign up to set email alerts
|

Blood Pressure and Its Relationship to Low Levels of Alcohol Consumption

Abstract: The association between average weekly alcohol consumption and blood pressure was studied in relation to age, adiposity and smoking in 13 535 men and 7385 women. There was a progressive increase in blood pressure with increasing alcohol consumption, even at low levels of consumption.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

1986
1986
2013
2013

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(9 citation statements)
references
References 4 publications
0
9
0
Order By: Relevance
“…Some of these studies suggest a positive linear relationship with the level of alcohol intake, starting from zero consumption, after accounting for smoking and other confounders (Arkwright et al 1982;Cooke et al 1983). A large-scale prospective study found that women drinking 20-34 g alcohol/d had a relative risk of 1•4 compared with non-drinkers for having developed hypertension at 4-year follow-up, independent of smoking and dietary variables (Witteman et al 1990).…”
Section: Blood Pressurementioning
confidence: 99%
“…Some of these studies suggest a positive linear relationship with the level of alcohol intake, starting from zero consumption, after accounting for smoking and other confounders (Arkwright et al 1982;Cooke et al 1983). A large-scale prospective study found that women drinking 20-34 g alcohol/d had a relative risk of 1•4 compared with non-drinkers for having developed hypertension at 4-year follow-up, independent of smoking and dietary variables (Witteman et al 1990).…”
Section: Blood Pressurementioning
confidence: 99%
“…Whether or not low to moderate levels of drinking are associated with elevated blood pressure is controversial. Some population cohort14 and cross-sectional studies58 reported a positive association between levels of alcohol consumption and blood pressure, even from the lowest levels of consumption 912. Other studies revealed a J-shaped or U-shaped alcohol-blood pressure association 1315.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, the evidence that even a little alcohol will raise the blood pressure has become equally convincing (30,8,46), as seen in the report on 20,920 persons not receiving antihypertensive therapy screened at the Sydney, Australia Hospital (8). Blood pressures were progressively higher with increas ing alcohol consumption, and the relationship was even closer after statistical correction for age, obesity, and smoking.…”
Section: Alcoholmentioning
confidence: 65%